Reverse transcription through a bulky triazole linkage in RNA: implications for RNA sequencing - Chen, X; El-Sagheer, A; Brown, T (Royal Society of Chemistry, 2014)
A triazole linkage is formed in RNA by untemplated strain-promoted or CuAAC chemical ligation of 3'-azide and 5'-cyclooctyne oligonucleotides under denaturing conditions. Reverse transcriptase reads through these artificial linkages with omission of one nucleotide. These surprising results have implications for RNA isolation, amplification, sequencing and a variety of biological applications.